Product market cooperation under efficient bargaining with different disagreement points: a result - Buccella, Domenico (Economics and Business Review, 2015)
This paper analyzes the effects of product market cooperation in a duopoly with homogeneous goods. Labor unions and firms are locked in bilateral monopoly relations and bargaining within the industry takes place under the efficient bargaining (EB) model. The paper discusses the role of different firms’ disagreement payoff on bargaining outcomes and their effect on social welfare components. It shows that the disagreement point of firms can play a crucial role in solving potential conflicts of interest between unions and firms concerning bargaining issues.